Unauthorised Functioning of Healthcare Institutes and Loss of Revenue - CAG of India (CAG of India)
Failure to renew the licenses of the Nursing Homes/ Clinical establishments and recover the licenses renewal fee resulted in unauthorised functioning of these establishments and non-recovery of revenue of INR 0.44 crore.